INDONESIAN AFFIXATION ATTACHED TO ENGLISH WORDS IN POCONGGG JUGA POCONG - Kusuma, Dimas Setya (2014)
This paper analyzes the pattern of Indonesian affixation which is attached to English words found in the book Poconggg Juga Pocong written by @poconggg. The data were collected by reading the novel and taking notes of English words that are being attached by Indonesian affixes. The patterns of those words were analyzed whether or not the affixation changed the word class of English words. From the analyses, it is revealed that Indonesian affixation can be attached to English words. After being attached to English words, Indonesian affixes changed the word class of English words. Keywords: affixation, affix, prefix, suffix, English, Indonesia.